2020
DOI: 10.2337/dc20-0735
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid Expansion and Utilization of Antihyperglycemic Therapies

Abstract: Certain antihyperglycemic therapies modify cardiovascular and kidney outcomes among patients with type 2 diabetes, but early uptake in practice appears restricted to particular demographics. We examine the association of Medicaid expansion with use of and expenditures related to antihyperglycemic therapies among Medicaid beneficiaries. RESEARCH DESIGN AND METHODSWe employed a difference-in-difference design to analyze the association of Medicaid expansion on prescription of noninsulin antihyperglycemic therapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…The ACA Medicaid expansion was designed to address high uninsured rates among low-income adults who fall into the coverage gap. The findings of this study confirm and complement the earlier studies that found that the ACA Medicaid expansion was associated with improved care and control of diabetes [ 15 - 17 ].…”
Section: Discussionsupporting
confidence: 89%
“…The ACA Medicaid expansion was designed to address high uninsured rates among low-income adults who fall into the coverage gap. The findings of this study confirm and complement the earlier studies that found that the ACA Medicaid expansion was associated with improved care and control of diabetes [ 15 - 17 ].…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have found that cost sharing, formulary restrictions and Medicaid expansion are associated with utilization of newer diabetes medications. 7 The relationship between insurance coverage and access to newer diabetes medications requires further study.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 Further, among patients with diabetes, minority race/ethnicity and lower socioeconomic status are associated with greater cost-limited access of diabetes medications. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…Given this accumulating evidence, multiple major societies have been updating recommendations in recent years with strong directives for the use of these glucose-lowering agents with proven cardiovascular benefits . Older studies demonstrated low early use of SGLT2i and GLP-1 RA . Whether uptake of these agents has improved with early adoption of these recommendations is unknown.…”
Section: Introductionmentioning
confidence: 90%